Evaluation of Movement Restriction Zone Sizes in Controlling Classical Swine Fever Outbreaks - Yadav, Shankar; Olynk Widmar, Nicole; Lay, Donald C.; Croney, Candace; Weng, Hsin-Yi (Frontiers in Veterinary Science, 2017)
The objective of this study was to compare the impacts of movement restriction zone sizes of 3-km, 5-km, 9-km, and 11-km with that of 7-km (the recommended zone size in the United States) in controlling a classical swine fever (CSF) outbreak. In addition to zone size, different compliance assumptions and outbreak types (single-site and multiple-site) were incorporated in the study. Three assumptions of compliance level were simulated: baseline, baseline ±10%, and baseline ±15%. The compliance level was held constant across all zone sizes in the baseline simulation. In the baseline ±10% and baseline ±15% simulations, the compliance level was increased for 3-km and 5-km and decreased for 9-km and 11-km from the baseline by the indicated percentages. The compliance level remained constant in all simulations for the 7-km zone size. Four single-site (i.e., with one index premises at the onset of outbreak) and four multiple-site (i.e., with more than one index premises at the onset of outbreak) CSF outbreak scenarios in Indiana were simulated incorporating various zone sizes and compliance assumptions using a stochastic between-premises disease spread model to estimate epidemic duration, percentage of infected, and pre-emptively culled swine premises. Furthermore, a risk assessment model that incorporated the results from the disease spread model was developed to estimate the number of swine premises under movement restrictions that would experience animal welfare outcomes of overcrowding or feed interruption during a CSF outbreak in Indiana. Compared with the 7-km zone size, the 3-km zone size resulted in a longer median epidemic duration, larger percentages of infected premises and pre-emptively culled premises (P’s <.001) across all compliance assumptions and outbreak types. With the assumption of a higher compliance level, the 5-km zone size significantly (P <.001) reduced the epidemic duration and percentage of swine premises that would experience animal welfare outcomes in both outbreak types. Whereas assumption of a lower compliance level for 9-km and 11-km zone sizes significantly (P <.001) increased the epidemic duration and percentage of swine premises with animal welfare outcomes compared with the 7-km zone size. The magnitude of impact due to a zone size varied across the outbreak